2009
DOI: 10.1897/08-291.1
|View full text |Cite
|
Sign up to set email alerts
|

Temperature as a toxicity identification evaluation tool for pyrethroid insecticides: Toxicokinetic confirmation

Abstract: Toxicity identification evaluation (TIE) methods can be used to identify toxic compounds in environmental samples using a variety of laboratory techniques. Whereas TIEs exist for nonpolar organics, relatively few methods are established for individual contaminant classes. Toxicity identification evaluations have shown pesticides to be the cause of toxicity in agricultural waters and effluents, and more recent studies have shown that the insecticide class of concern is pyrethroids. The primary objectives of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
102
2
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 158 publications
(112 citation statements)
references
References 30 publications
7
102
2
1
Order By: Relevance
“…Physical effects of DDT, also a neurotoxin, increase at lower temperatures because nerve sensitivity increases ). Conversely, raising water temperature by 1°C to 2°C caused 1.5-to 100-fold increases in the toxicity of metals, carbamates, organophosphates (including chlorpyrifos), and some organochlorines other than DDT (Lydy et al 1990;Boening 2000;Heugens et al 2001;Harwood et al 2009). Large increases in susceptibility to toxins can occur when metabolic rates elevated by warmer temperatures increase uptake of pollutants.…”
Section: Potential Effects Of Climate Changementioning
confidence: 99%
“…Physical effects of DDT, also a neurotoxin, increase at lower temperatures because nerve sensitivity increases ). Conversely, raising water temperature by 1°C to 2°C caused 1.5-to 100-fold increases in the toxicity of metals, carbamates, organophosphates (including chlorpyrifos), and some organochlorines other than DDT (Lydy et al 1990;Boening 2000;Heugens et al 2001;Harwood et al 2009). Large increases in susceptibility to toxins can occur when metabolic rates elevated by warmer temperatures increase uptake of pollutants.…”
Section: Potential Effects Of Climate Changementioning
confidence: 99%
“…However, earlier studies reported 10-d LC50 of chlorpyrifos for Chironomus tentans of 9956 µg/kg OC (Ankley et al, 1994) and for Chironomus dilutus of 10,800 µg/kg OC (Harwood et al, 2009), which is almost two times higher than our study (4500 µg/kg OC).…”
Section: Risk Assessmentcontrasting
confidence: 96%
“…Chlorpyrifos water concentration reached a peak level of 8.36 ng/L assuming no air-to-water gaseous exchange occurred, and this concentration was significantly lower than the 4-d water-only median lethal concentration for C. dilutus of 459 ng/L (Harwood et al, 2009). In total, the air to water to sediment transport of chlorpyrifos suggested that its dynamic transport would decrease human inhalation exposure risk, but had little influence on its aquatic toxicity.…”
Section: Implications For a Regional Risk Assessmentmentioning
confidence: 88%